FAKTOR–FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MEMUTUSKAN MEMBELI AIR MINUM DALAM KEMASAN MEREK AMIA PADA PT AMANAH INSANILLAHIA CABANG PEKANBARU - Ridho Saputra; Indra Safri (VALUTA, 2016)
The purpose of this study is : to analyze and explain consumer behavior that influence consumer buyinginterest in PT Amanah Insanillahia Amia Pekanbaru branch . While the formulation of this problem ishow to influence consumer behavior towards buying interest or decide to buy bottled water brand AmiaPT Amanah branch Insanillahia Pekanbaru . The methods used are : research locations , types and sourcesof data , primary and secondary data , the population in this study include consumer Amia PT Amanahbranch Insanillahia Pekanbaru totaling 37 people. Data collection techniques and analysis ofquestionnaires and interviews and quantitative descriptive data . This study concluded that the results offilling the questionnaire by the respondents of this study which is the consumer , the motivation,personality , self-concept , knowledge , culture , characteristics , families , groups , technology at PTAmanah branch Insanillahia Pekanbaru is concluded in the category of agree . Of the nine factors can beseen that the most dominant factors and variables affect the behavior of konsumenn PT Amanah branchInsanillahia Pekanbaru is the motivating factor . Therefore, researchers suggest the company will alsoneed to pay attention to every consumer complaints that the relationship between the customer and thecompany can be established and the complaint can be used as an encouragement or motivation andbecome better than ever.